2019
DOI: 10.7567/1882-0786/aafca2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of internal quantum efficiency in GaInN-based light-emitting diode under electrical injection: carrier recombination dynamics analysis

Abstract: We proposed a method to determine the internal quantum efficiency (IQE) of GaInN-based light-emitting diode (LED). For the accurate determination thereof, we carefully reviewed a conventional carrier rate equation and then proposed a set of advanced formulae, which can comprehensively explain the carrier dynamics in a modern GaInN-based LED. Based on our proposed formula, this convenient method to determine the IQE is presented. Next, to identify the proposed carrier rate equations and recombination dynamics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Note that the EQEs at 50 mA are estimated as ~15.8% and ~11.5% for LED A and LED B, respectively. Recently, we proposed a reliable and convenient method to determine the IQE of GaInN-based LEDs [38]. The method is based on finding an exact value of the light extraction efficiency (LEE) by analyzing the L-I curve with an advanced carrier dynamics equation, which obtains the IQE values by comparing the EQEs, i.e., IQE = EQE × LEE.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the EQEs at 50 mA are estimated as ~15.8% and ~11.5% for LED A and LED B, respectively. Recently, we proposed a reliable and convenient method to determine the IQE of GaInN-based LEDs [38]. The method is based on finding an exact value of the light extraction efficiency (LEE) by analyzing the L-I curve with an advanced carrier dynamics equation, which obtains the IQE values by comparing the EQEs, i.e., IQE = EQE × LEE.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the IQEs in Fig. 2 were evaluated by the method presented in our previous paper 3,30 . As expected, the IQE gradually decreases with elevating chamber temperature over the entire current range.…”
Section: Experimental Results Analysis and Discussionmentioning
confidence: 99%
“…Meanwhile, recent studies revealed that recombinations that occurs outside the active region predominates at high-current injection in GaInN-based LEDs. In this study, we thus utilized AB + f ( n ) model 30 , 35 , 36 , which is frequently adopted to comprehensively explain recombinations occurring both inside and outside the active region. In this model, the IQE is written in terms of the carrier rate equation as following, where T is the temperature, A ( n,T ) and B ( n,T ) are the SRH nonradiative recombination and the bimolecular radiative recombination coefficient in MQWs.…”
Section: Experimental Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Важнейшим параметром светодиодов, определяющим эффективность преобразования электрического тока в оптическое излучение, является внутренний квантовый выход. Этот параметр используется при оценке качества изготовления светодиодных гетероструктур, их энергетической эффективности, а также при исследовании механизмов спада эффективности излучения при больших токах и механизмов деградации светодиодов в процессе их испытаний [1][2][3][4][5]. Внутренний квантовый выход определяется как отношение числа фотонов, рожденных в активной области светодиода в единицу времени, к числу инжектированных в эту область электронов [1].…”
Section: Introductionunclassified